PENGARUH DAYA GELOMBANG MIKRO DAN RASIO BAHAN-PELARUT PADA RENDEMEN DAN SIFAT FISIKOKIMIA PEKTIN DARI KULIT BUAH KAKAO - Pranayasa, W. Angga; Putra, G. P. Ganda; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 10 No 2 (2022): Juni, 2022)
Cocoa pod ( Theobroma cacao L.) are composed of 75% cocoa husk which is discarded as waste during the processing of cocoa beans. Utilization of cocoa husk has been studied, including as a source of pectin. Conventional pectin extraction tends to take a long time, so it is necessary to develop a new method. Microwave-assisted extraction (MAE) is used because it is more efficient. In this study, the effect of microwave power and cocoa husk-solvent ratio on the yield and characteristics of pectin was investigated. This research also determines the best combination to produce pectin from cocoa pod husk. Extraction was carried out for 6 minutes with 0.1 N hydrochloric acid (HCl) at microwave power (600 and 800 W) and cocoa husk-solvent ratio (1:20, 1:30 and 1:40 w/v). The results showed that both factors affected the characteristics of the pectin except water content. The optimum conditions for extracting pectin from cocoa pod husk were at 800 W microwave power and 1:30 (w/v) cocoa husk-solvent ratio. Pectin produced was 2.63 g per 100 g of dried cocoa husk and was grouped into low methoxyl and high ester pectin. The characteristics of pectin such as moisture content, ash content, equivalent weight, methoxyl content, galacturonic acid content and degree of esterification is 15.57±1.23%, 2.43±0.12%, 765.3±17.08 mg, 4.83±0.18%, 50.4±0.54% and 54.4±1.51%, respectively.